Voltage-Dependent Anion Selective Channel Isoforms in Yeast: Expression, Structure, and Functions - Di Rosa, Maria Carmela; Guarino, Francesca; Conti Nibali, Stefano; Magrì, Andrea; De Pinto, Vito (Frontiers in Physiology, 2021)
Mitochondrial porins, also known as Voltage-Dependent Anion selective Channels (VDACs), are pore-forming molecules of the outer mitochondrial membranes, involved in the regulation of metabolic flux between cytosol and mitochondria. Playing such an essential role, VDAC proteins are evolutionary conserved and isoforms are present in numerous species. The quest for specific function(s) related to the raise of multiple isoforms is an intriguing theme. The yeast Saccharomyces cerevisiae genome is endowed with two different VDAC genes encoding for two distinct porin isoforms, definitely less characterized in comparison to mammalian counterpart. While yVDAC1 has been extensively studied, the second isoform, yVDAC2, is much less expressed, and has a still misunderstood function. This review will recapitulate the known and poorly known information in the literature, in the light of the growing interest about the features of VDAC isoforms in the cell.